Growth and characterization of GaN nanostructures under various ammoniating time with fabricated Schottky gas sensor based on Si substrate. (May 2018) - Abdullah, Q.N.; Ahmed, A.R.; Ali, A.M.; Yam, F.K.; Hassan, Z.; Bououdina, M.; Almessiere, M.A.
Abstract: This paper presents the investigation of the influence of the ammoniating time of GaN nanowires (NWs) on the crystalline structure, surface morphology, and optical characteristics. Morphological analysis indicates the growth of good quality and high density of NWs with diameters around 50 nm and lengths up to tens of microns after ammoniating for 30 min. Structural analysis shows that GaN NWs have a typical hexagonal wurtzite crystal structure. Raman spectroscopy confirms the formation of GaN compound with the presence of compressive stress. Photoluminescence (PL) measurements revealed two band emissions, an UV and a broad visible emission. Hydrogen sensor was subsequently fabricated by depositing Pt Schottky contact onto GaN NWs film. The sensor response was measured at various H2 concentrations ranged from 200 up to 1200 ppm at room temperature. It was found that the response increases significantly for low H2 concentration (200–300 ppm) to reach about 50% then increases smoothly to reach 60% at 1200 ppm. The as-fabricated sensor possesses higher performances as compared to similar devices reported in the literature. Highlights: Different nanostructures of GaN deposited on Si. At different duration of annealing GaN NWs exhibit different density of NWs. GaN NWs shows capability to detect low concentration down to 200 ppm with a response of 43.5% at RT.